1989
DOI: 10.1128/jvi.63.2.481-492.1989
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of the cellular src gene and 3' adjacent sequences in avian sarcoma virus PR2257

Abstract: When injected into chickens, a transformation-defective mutant of the Prague C strain of Rous sarcoma virus induced tumors at low incidence and after a long latency. One such tumor released a replication-defective virus designated PR2257. We molecularly cloned and sequenced the proviral DNA from quail fibroblasts transformed by PR2257. Comparison of PR2257 sequence with that of Prague C, cellular src, and 3' adjacent cellular DNA showed that the spliced version of the c-src gene and about 950 base pairs (bp) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 69 publications
2
2
0
1
Order By: Relevance
“…Partial analysis of exonintron organization of the chicken c-Rmil gene showed that only this 37-bp exon allows an in-frame junction between the six gag amino acids in the leader sequence and the entire c-Rmil kinase domain. Similar structures at the 5' ends of two retroviruses, Si and PR2257, which transduced the c-src gene in vivo, were described previously (11,16). Therefore, constitution of 5' ends by a splice process could represent a general mechanism in retrovirus transduction of proto-oncogenes.…”
Section: Discussionsupporting
confidence: 62%
“…Partial analysis of exonintron organization of the chicken c-Rmil gene showed that only this 37-bp exon allows an in-frame junction between the six gag amino acids in the leader sequence and the entire c-Rmil kinase domain. Similar structures at the 5' ends of two retroviruses, Si and PR2257, which transduced the c-src gene in vivo, were described previously (11,16). Therefore, constitution of 5' ends by a splice process could represent a general mechanism in retrovirus transduction of proto-oncogenes.…”
Section: Discussionsupporting
confidence: 62%
“…Similar structures were recently described in the 5' ends of two viruses which transduced the c-src gene (13,22). It is possible that the transduction of c-mil proceeded by the integration of RAV-1 provirus upstream of exon 8 of c-mil and the cotranscription of viral and c-mil sequences.…”
Section: Genomessupporting
confidence: 62%
“…Mechanism of c-mil transduction. There have been several reports on in vivo transduction of proto-oncogenes, including src (13,18,22), fps (35), erbB (21,32), and fos (36), by ALV. A general model for a multistep transduction of proto-oncogenes by ALV has been proposed (49).…”
Section: Genomesmentioning
confidence: 99%
“…Although hybrid virus-Aonc-poly(A) RNAs were previously described in avian lymphomatosis virus-infected cells (8,17), they were never shown to give rise to retroviruses. Conversely, similar 5' junctions were found in two avian sarcoma viruses which transduced the c-src gene in vivo (7,11). Therefore, splicing between viral leader and cellular sequences may represent a common mechanism for generating 5' junctions during the transduction process.…”
Section: Fig 1 (A)mentioning
confidence: 74%